Adarsh primary health care yojana in Rajasthan - Chauhan, Mamta (International Journal Of Community Medicine And Public Health, 2020)
Primary health care (PHC) center is the first point of contact between community and the medical officer at village level. The PHCs have been envisaged to provide an integrated curative and preventive health care to the rural population with emphasis on preventive and promotive aspects of health care. The PHCs are established and maintained by the State Governments under the minimum needs programme or basic minimum services programme. At present, a PHC is manned by a medical officer supported by paramedical and other staff. It acts as a referral unit for 4 to 6 sub centres. It has 6 beds for patients. The activities of PHC involve curative, preventive, promotive and family welfare services. There are 2080 PHCs functioning as on March, 2018 in the Rajasthan.